Rekonstruksi Keharmonisan Keluarga dalam Perspektif Family Systems Theory Murray Bowen: Integrasi Psikologi Keluarga dan Hukum Keluarga Islam - Ahmad Warid Wajdil Haq; Sariatul Fikri (Universitas Islam Negeri Sumatera Utara, 2026)
Family harmony is a fundamental pillar in establishing individual well-being, social resilience, and sustainable national development. Nevertheless, increasing rates of marital conflict, divorce, domestic violence, and psychosocial challenges indicate that contemporary family resilience cannot be adequately explained solely through normative legal perspectives. Existing studies on Murray Bowen's Family Systems Theory generally emphasize psychological counseling and family therapy, while Islamic family law scholarship predominantly focuses on juridical aspects of rights and obligations. Few studies have attempted to integrate these two disciplinary perspectives into a comprehensive conceptual framework for family harmony. This study aims to analyze the concept of family harmony based on Murray Bowen's Family Systems Theory, examine its relevance to Islamic family law principles, and reconstruct an integrative model of family harmony grounded in both family psychology and Islamic legal values. This research employs normative legal research using conceptual, philosophical, and interdisciplinary approaches through qualitative analysis of primary and secondary legal and scientific literature. The findings demonstrate that Bowen's concepts of self-differentiation, emotional system, triangulation, emotional cutoff, and multigenerational transmission remain highly relevant in explaining emotional dynamics within Muslim families. However, these psychological dimensions require normative reinforcement through Islamic family law principles emphasizing justice (al-'adl), mutual responsibility, sakinah, mawaddah, raḥmah, and the realization of maqāṣid al-sharī'ah. This study proposes an integrative reconstruction model positioning family harmony as the outcome of balanced emotional maturity, legal responsibility, and ethical-religious values. The proposed framework contributes to strengthening interdisciplinary discourse on family resilience and offers a theoretical foundation for developing Islamic family counseling and family law policies in contemporary Muslim societies.